The "art" of teaching study skills: a teacher or a student as a homo hubris in media space? - Marta Wrońska (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introdaction Dynamic cultural, economical, or scientific and technical transitions enforce transformation in educational processes. Currently, teaching study skills cannot be considered as simple field and certainly not a pleasant one. Nowadays, learning process does not consist in executing an educational programme rigidly, but in responding to emerging problems and in ability to create the right conditions to resolve them. Research Aim Key questions were important in the research: What are constituent elements 'art' of teaching study skills at school?? and will they aid the development of modern personality referred to as a homo hubris? Who in media space can be described as a homo hubris? Research tools Tests diagnosing the declared knowledge on media of the adolescents and teachers, and their procedure knowledge connected with abilities to use the media and also a scale for examining attitudes towards media).  Results and Conclusion The results are not encouraging. The teachers who participated in my research fared worse than their students in all three areas I described. Hhomo hubris in the media space is adolescent. Moreover, the respondents' knowledge of contemporary media is selective and limited, and their skills are reduced to only basic operations. Keywords: The  'art' of teaching study skills, and its atributes, modern man concept, modern personality traits, media space, own research.